"Maybe black girls do yoga": A focus group study with predominantly low-income African-American women. (October 2018) - Tenfelde, Sandi M.; Hatchett, Lena; Saban, Karen L.
Highlights: African American women are seeking healthy ways to manage stress. Yoga and mindfulness are potential strategies to help communities address mental health needs. Women identified benefits and barriers to yoga and mindfulness practices and offered suggestions and solutions for engagement. Abstract: Objective: To explore African American (AA) women's use of mind-body therapies, such as yoga and mindfulness, and factors that impact their experiences, observations and opinions. Design: Focus groups were conducted to better understand how AA women perceive mind-body therapies and how to best bring these interventions into their community. Interviews were audiotaped and transcribed. Setting: The urban Midwest. Outcome measures: In addition to qualitative outcomes, descriptive measures included the Perceived Stressor Scale, Beliefs About Yoga Scale, and Determinants of Meditation Practice Inventory (DOMPI). Results: Twenty-two, predominantly low-income (75% reported income <$50, 000) and single (82%) women participated in three age stratified focus groups (18–34 years, 35–65 years, 66 years and older). Participants acknowledged life stress and shared common coping mechanisms. They recognized that yoga and mindfulness could be beneficial and discussed barriers to practice (including personal and structural). Younger women reported more time constraints as barriers, middle aged women had more experience with yoga, and older women identified the spiritual component to yoga/mindfulness as potentially conflicting with current coping strategies. Participants suggested ways to share mind-body therapies within the AA community along with solutions for engagement. Conclusions: AA women acknowledged stress in their lives and recognized the need for additional coping measures. Although women reported interest in yoga/mindfulness they identified barriers, including limited access to convenient classes, and offered suggestions for bringing yoga and mindfulness to their communities.